Fluence to local skin absorbed dose and dose equivalent conversion coefficients for monoenergetic positrons using Monte-Carlo code MCNP6. (January 2016) - Bourgois, L.; Antoni, R.
Abstract: Conversion coefficients fluence to local skin equivalent dose, as introduced in ICRP Publication 116, 2010, are calculated for positrons of energies ranging from 10 keV to 10 MeV using the code MCNP6. Fluence to dose equivalent conversion coefficients H′ (0.07, 0°)/ Φ are calculated for positrons of energy ranging between 20 keV and 10 MeV. A comparison between operational dose quantity H ′(0.07, 0°) and the Local-Skin equivalent Dose shows an overall good agreement between these two quantities, except between 60 keV and 100 keV. Highlights: Local Skin equivalent Dose (LSD), are calculated for positrons using the code MCNP6. LSD shows an overall good agreement with operational quantities except between 60 keV and 100 keV. Difference between electrons and positrons in the range 10 to 60 keV (annihilation)